Improved quality of life and pain relief in mature horses with osteoarthritis after oral transmucosal cannabidiol oil administration as part of an analgesic regimen - Interlandi, Claudia; Tabbì, Marco; Di Pietro, Simona; D’Angelo, Fabiola; Costa, Giovanna L.; Arfuso, Francesca; Giudice, Elisabetta; Licata, Patrizia; Macrì, Daniele; Crupi, Rosalia; Gugliandolo, Enrico (Frontiers in Veterinary Science, 2024)
Osteoarthritis is a common pathology in horses, often resulting in various signs of distress, such as avoidance of touch, varying degrees of lameness, reluctance to move, and disappetence. The use of hemp oil products containing cannabidiol (CBD) is increasing in popularity among horse owners, despite limited clinical data on their long term safety and use being available. To investigate the therapeutic potential of hemp oil supplemented with 15% CBD as part of a classical analgesic protocol, a study was conducted on twenty horses suffering from mild osteoarthritis. Hemp oil with 15% CBD was shown to reduce pain and inflammation and improve the health of treated horses.